PRAGMATIC APPROACH UPON THE INSTITUTIONAL EDUCATIONAL VERBALINTERACTION - Bălănescu, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The present paper intends to analyze the institutional educational verbal interaction from the pragmatics point of view, as pragmatics is that linguistic discipline focused on the dialogized communication performed by real speakers: the teacher (instructor, trainer) and his students. I was interested in emphasizing the type of verbal; interaction established during this special form of communication, the way the principles of communication are kept or broken during the dialogue between teacher and student, different types of discourse performed by the teacher while discussing with his students. I was also interested in underlining the role of the deictic elements (especially the subjective ones) in the communication performed within the didactic process of teaching-learning. The present paper intends to outline the importance of pragmatics in achieving an efficient teaching-learning process for the both sides implied: both for the teachers who will succeed in teaching easier their subject matters, and for the students who will understand faster the theoretic concepts and thus will be able to turn them into efficient and useful knowledge for their future career. Owing to my university teaching experience, I have faced lots of situations when pragmatics helped me out. In this paper I will focus my attention upon my didactic activities performed when teaching the Romanian language for foreign students (as I also teach Pragmatics, Advertising and Politic Discourse to the Romanian students of my Faculty). The present paper contains four parts as it follows: introduction, literature review, case study and conclusions (accompanied by limitations of the paper and recommendations).